High-Rate Performance Solid-State Lithium Batteries with Silica-Gel Solid Nanocomposite Electrolytes using Bis(fluorosulfonyl)imide-Based Ionic Liquid. Issue 7 (2nd April 2020) - Sagara, Akihiko; Chen, Xubin; Gandrud, Knut B.; Murata, Mitsuhiro; Mees, Maarten; Kaneko, Yukihiro; Arase, Hidekazu; Vereecken, Philippe M.
Abstract : A nanocomposite electrolyte composed of a non-volatile ionic liquid, organic Li-salt and porous-inorganic material can be a promising option as a solid electrolyte material. We present a high-rate performance in solid-state lithium metal and Li-ion batteries using a silica-gel solid nanocomposite electrolyte (nano-SCE) made by the sol-gel method with a bis(fluorosulfonyl)imide (FSI)-based ionic liquid. The nano-SCE, composed of 1-ethyl-3-methylimidazolium bis(fluorosulfonyl) imide (EMI-FSI) and Li-FSI confined in the mesoporous silica matrix, exhibits an ionic conductivity of 6.2 mS cm −1 at room temperature. The capacity of the Li-LiFePO4 cell using the EMI-FSI based nano-SCE reaches 150 mAh g −1 at 0.1C and 113 mAh g −1 at 1C, which is higher than that achieved by the other reported batteries that use a similar composite electrolyte. The C-rate performance of the prepared solid batteries is comparable to that of cells with the conventional lithium hexafluorophosphate (LiPF6 ) electrolyte. Our results show that impregnation of a liquid precursor is an efficient approach for an excellent electrode/electrolyte interface contact in the solid composite electrode as the reaction kinetics at the interface of the active mass and nano-SCE are sufficiently fast, and thus is advantageous compared with the other types of solid electrolytes.